2015
DOI: 10.1007/s13277-015-3506-z
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide phosphorybosiltransferase overexpression in thyroid malignancies and its correlation with tumor stage and with survivin/survivin DEx3 expression

Abstract: Nicotinamide phosphorybosiltransferase (NAMPT) plays an important role in the regulation of cellular growth, angiogenesis, and apoptosis in mammalian cells. NAMPT overexpression has been recently found in colorectal, breast, prostatic, gastric, esophageal, pancreatic cancers, and specific NAMPT inhibitors might be adjuvant therapeutic modalities. In this study, we analyzed NAMPT expression in 40 malignant and in 67 benign thyroid tissue samples using qPCR. We also investigated relationships between NAMPT expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 32 publications
2
56
0
Order By: Relevance
“…To the best of our knowledge, this is the first study evaluating survivin DEx3 IHC expression in thyroid lesions. These findings are in agreement with our previous studies showing overexpression of survivin DEx3 mRNA in thyroid cancer (19,20). Using RT-qPCR, the present study also observed a positive association between the overexpression of survivin DEx3 mRNA and tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study evaluating survivin DEx3 IHC expression in thyroid lesions. These findings are in agreement with our previous studies showing overexpression of survivin DEx3 mRNA in thyroid cancer (19,20). Using RT-qPCR, the present study also observed a positive association between the overexpression of survivin DEx3 mRNA and tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, anti-apoptotic survivin DEx3 is suggested to be associated with tumor aggressiveness, advanced stage and poor prognosis in numerous types of cancer (5). We have previously reported survivin and its DEx3 mRNA variant overexpression in thyroid cancer (19,20).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In cancer cells, NAMPT plays a crucial role in several physiological processes including energy generation, reductive biosynthesis, mitochondrial function, and the response to oxidative stress (1,(12)(13)(14). It is also overexpressed in several types of tumors (8,(15)(16)(17)(18)(19) and its expression appears to be associated with tumor progression (15,20). The inhibition of NAMPT leads to the attenuation of tumor growth and induction of apoptosis (11; 21-24).…”
Section: Introductionmentioning
confidence: 99%